Charge transfer behavior of triboelectric polymers and triboelectric sensors operated under ultrahigh pressure - Jun Hu; Zhaoqi Liu; Peng Yang; Siyao Qin; Ning Li; Wenyu Ji; Zhong Lin Wang; Xiangyu Chen (SusMat)
Abstract The energy generation performance of triboelectric materials under ultrahigh pressure remains to be investigated. Here, the variations in molecular structure and built‐in electric field of triboelectric polymers under ultrahigh pressure have been thoroughly studied. The attenuation of built‐in electric field and the escaping of triboelectric charges under ultrahigh pressure are observed in different triboelectric polymers, whereas the existence of deep traps allows the built‐in electric field to be recoverable with the release of pressure. Moreover, the macromolecular conformational changes, including twisting molecular chains and crystal structure changes, can also induce the redistribution of deep traps, leading to a sudden increase in built‐in electric field under specific pressure. Finally, a triboelectric sensor for ultrahigh pressure condition is fabricated with excellent cycle repeatability and a total thickness of 2 mm, which has a sensitivity of 0.07 V MPa−1 within a linear region of 1–100 MPa. This study offers in‐depth insight into the physical understanding of charge behavior both on interface and in bulk of triboelectric materials, whereas the proposed ultrahigh pressure sensors can promote various potential applications of triboelectric sensor in extreme environments.